Micromagnetic Determination of the FORC Response of Paleomagnetically Significant Magnetite Assemblages - Nagy, Lesleis; Moreno, Roberto; Muxworthy, Adrian R.; Williams, Wyn; Paterson, Greig A.; Tauxe, Lisa; Valdez‐Grijalva, Miguel A. (2024)
Fil: Nagy, Lesleis. University of Liverpool. Department of Earth, Ocean and Ecological Sciences; United Kingdom.